The general interference model in the fuzzy reliability analysis of systems - Pho, Nguyen Van (Vietnam Journal of Mechanics, 2005)
The interference model of the fuzzy reliability analysis has been the focus of some researches. In this paper, the author proposed a general interference model for fuzzy reliability analysis, which based on the safety condition, not use the stress-strength interference model. Therefore, the proposed model can apply for every reliability problems of the systems.